Microwave Absorber Properties \ce {La_{0.67}Sr_{0.33}Mn_{0.8}Ni_{0.2}O3} Using Sol Gel Synthesis Methods - Laksanawati, Wahyu Dian; Kurniawan, Budhy (Omega: Jurnal Fisika dan Pendidikan Fisika, 2017)
This paper reports the process and the results are supplemented by material microwave absorber characterisation \ce {La_{0.67}Sr_{0.33}Mn_{0.8}Ni_{0.2}O3} which has been synthesised by sol gel method. Results refinement of the XRD data showed that the material \ce {La_{0.67}Sr_{0.33}Mn_{0.8}Ni_{0.2}O3} have formed a single phase. From the results of using the software refinement High Score obtained crystal size on sample of 21.18 nm. Number of spin concentration in the sample at ESR test results showed a decrease when doping Ni increased, the area under the curve of absorption decreases as 388.718. This is due to the substitution of \ce {Ni^{2+}} ions \ce {Mn^{3+}} ions thus inhibiting electron hopping of electrons $e_g$ (\ce {Mn^{3+}} ion) to $\mathrm{t_{2g}}$ (\ce {Mn^{4+}} ion) in the mechanism of double exchange so that the spin of the electrons will $\mathrm{t_{2g}}$ antiparallel. Competition between ferromagnetic properties with antiferromagnetic spin make will change the direction so that the sample magnetisation will decrease and the magnetic moments become random. ESR results are used to confirm the results of the VNA. Microwave absorption ability is indicated by the value of reflection loss on the sample is $-66.67$ dB.